Effect of Lactobacillus rhamnosus HN001 on carriage of Staphylococcus aureus: results of the impact of probiotics for reducing infections in veterans (IMPROVE) study - Eggers, Shoshannah; Barker, Anna K.; Valentine, Susan; Hess, Timothy; Duster, Megan; Safdar, Nasia (BMC infectious diseases, 2018)
Infection by Staphylococcus aureus (S. aureus) is a major cause of morbidity and mortality. Colonization by S. aureus increases the risk of infection. Little is known about decolonization strategies for S. aureus beyond antibiotics, however probiotics represent a promising alternative. A randomized controlled trial was conducted to determine the efficacy of Lactobacillus rhamnosus (L. rhamnosus) HN001 in reducing carriage of S. aureus at multiple body sites. One hundred thirteen subjects, positive for S. aureus carriage, were recruited from the William S. Middleton Memorial Medical Center, Madison, WI, USA, and randomized by initial site of colonization, either gastrointestinal (GI) or extra-GI, to 4-weeks of oral L. rhamnosus HN001 probiotic, or placebo. Nasal, oropharyngeal, and axillary/groin swabs were obtained, and serial blood and fecal samples were collected. Differences in prevalence of S. aureus carriage at the end of the 4-weeks of treatment were assessed. The probiotic and placebo groups were similar in age, gender, and health history at baseline. S. aureus colonization within the stool samples of the extra-GI group was 15% lower in the probiotic than placebo group at the endpoint of the trial. Those in the probiotic group compared to the placebo group had 73% reduced odds (OR 0.27, 95% CI 0.07-0.98) of methicillin-susceptible S. aureus presence, and 83% reduced odds (OR 0.17, 95% CI 0.04-0.73) of any S. aureus presence in the stool sample at endpoint. Use of daily oral L. rhamnosus HN001 reduced odds of carriage of S. aureus in the GI tract, however it did not eradicate S. aureus from other body sites. ClinicalTrials.gov Identifier: NCT01321606 . Registered March 21, 2011.